Dampak Negatif Rokok sebagai Ide Penciptaan Seni Grafis Stencil Print - Romi Yuneldi; Ariusmedi Ariusmedi (Departement of Mathematics Education, 2024)
This final work aims to visualize the negative impact of smoking in graphic artworks using the stencil print technique. The idea of this work is the visualization of the negative impacts caused by smoking, ranging from health, environmental, and social impacts. The method in the process of making this graphic art work goes through several stages, namely: preparation, elaboration, synthesis, concept realization, and completion. Each work has a size of 40cm x 52cm with the title of the work,